ON THE ANATOMY AND MORPHOLOGY OF FULL GROWN LARVA OF AMRABIPLOSIS ALLAHABADENSIS GROVER (CECIDOMYIIDAE : DIPTERA) - SINGH, SUMAN D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1992)
The larvae of gall midge lives inside the limited space of gall of mango leaf, due to which its movementis restricted and larva becomes sluggish hence all the system are not well developed. The muscles are developed weakly, but in comparision to the oblique and transverse muscles, the longitudinal muscles are much developed. The circulatory system consist of a long narrow uniform tube running from the metathoracic to the seventh abdominal segment, anteriorly it narrows down into an aorta upto the dorsal part of the brain. Two types of nephrocytes are visible viz. the pericardial and peripharyngeal. The central nervous systemis well developed. Many small and large size of fat bodies are arranged segmentally around the alimentary canal. At this stage there is no distinction of testis and ovaries in gonads. The imaginal discs are distinct and clearly visible.